Pandangan Awal: Tiga Konsep Ajaran Masyarakat Pegunungan dalam Teks Kidung Subrata - Prastowo Budi Purnama (Arnawa, 2025)
This article presents a philological study of Kidung Subrata (manuscript code L304 Peti 71 Roll 855/1), a Merapi–Merbabu scriptorium manuscript held by the National Library of Indonesia. Written on a frontal leaf in Buda script, the text belongs to the sisya lělana genre, narrating a protagonist’s journey of learning religious teachings in pursuit of spiritual perfection. Building on the author’s earlier research that examined bayu–śabda–hiḍěp, the present study extends the analysis by adding two further doctrinal concepts, oṅkāra and bañcana, as part of an initial mapping of nine teachings identified across the text. The research procedure consists of: (1) locating and selecting relevant textual fragments, (2) presenting a Latin transliteration based on a cleaned reading to avoid misleading spellings, (3) translating the passages into Indonesian, and (4) conducting content analysis supported by textual comparison with roughly contemporaneous sources (e.g., Sang Hyang Kamahāyanikan, Dharmapatañjala, and Bhima Svarga). The findings suggest that oṅkāra is framed as a generative principle of mystical syllables (leading to tryakṣara and pañcākṣara), bayu–śabda–hiḍěp functions as an integrated scheme of disciplined energy, speech, and mind for yogic practice, while bañcana is conceptualised as danger or deception arising from desire and attachment to material elements. Overall, the text conveys esoteric teachings through concise and symbolic formulations, making comparative reading essential for reconstructing its pedagogical framework. === Kajian ini merupakan kajian filologi menggunakan objek material naskah skriptorium Merapi-Merbabu yang berjudul Kidung Subrata dengan kode naskah L304 Peti 71 Rol 855/1. Naskah ini merupakan salah satu naskah koleksi Perpustakaan Nasional Republik Indonesia. Kidung Subrata ditulis menggunakan bahan material daun lontar atau rontal dan beraksara Buda. Teks ini memiliki genre Sisya Lelana atau cerita sastra yang berisikan perjalanan suatu tokoh dalam mempelajari berbagai ilmu pengetahuan dalam rangka mencari kesempurnaan hidup. Dalam penelitian sebelumnya yang dilakukan oleh penulis, teks Kidung Subrata berisikan konsep-konsep pengajaran Sivaisme. Dipenelitian sebelumnya, penulis menganalisis satu konsep pengajaran tersebut, yaitu bayu-śabda-hiḍěp. Untuk kajian saat ini, penulis menambahkan dua analiss konsep, yaitu konsep oṅkāra dan bañcana. Metode yang dilakukan adalah menggunakan hasil transliterasi edisi diplomatik dilanjutkan dengan menganalisis konsep-konsep tersebut dengan cara mengalihbahasakan dan mencari sumber pembanding untuk mempermudah analisis.